High-density SNP markers elucidate the genetic divergence and population structure of Noticiana sheep breed in the Mediterranean context - Chessari, Giorgio; Criscione, Andrea; Tolone, Marco; Bordonaro, Salvatore; Rizzuto, Ilaria; Riggio, Silvia; Macaluso, Vito; Moscarelli, Angelo; Portolano, Baldassare; Sardina, Maria Teresa; Mastrangelo, Salvatore (Frontiers in Veterinary Science, 2023)
Among livestock species, the sheep genetic resources have played an early major role in the Mediterranean area. Italy represents an important source of genetic resource, and, despite a dramatic contraction in numbers, still raise several local sheep populations that may represent a unique source of genetic diversity. The Noticiana is a population of the southeast part of Sicily appreciated both for its dairy products and for its resistance to harsh environment. In this study, the high-density Illumina Ovine SNP600K BeadChip array was used for the first genome-wide characterization of 48 individuals of Noticiana sheep with the aim of investigating its diversity, the genome structure and the relationship within the worldwide and Italian sheep breeds context. Moreover, the runs of homozygosity (ROH) pattern and the pairwise FST-outliers were examined. Noticiana reported moderate levels of genetic diversity. The high percentage of short and medium ROH segments (93% under 4 Mb) is indicative of a within breed relatedness dating back to ancient times despite the absence of management for the mating plans and the reduced population size. Multidimensional scaling, model-based clustering, the measurement of population differentiation and the neighbor-net showed the clear separation of Noticiana from the rest of the Italian sheeps, and highlighted ancestral genetic components shared with Comisana breed. This is probably the consequence of the combined effects of genetic drift, small population size and reproductive isolation. ROH islands and FST-outliers approaches in Noticiana identified genes and QTLs involved in milk and meat production, as well as related to the environment-adaptation capacity, and therefore are consistent with the phenotypic traits of the studied breed. Although a wider sampling could be useful to deeper the genomic survey on Noticiana, these results represent a crucial starting point for the characterization of an important local genetic resource, in the view of supporting local economy and preserve the biodiversity of the sheep species.